A novel asymmetric patch reflectarray antenna with ground ring slots for 5G communication systems - Jamaluddin, Mohd Haizal; Che Seman, Fauziahanim; Dahri, Muhammad Hashim; Abbasi, Muhammad Inam; Ashyap, Adel Yahya Isa; Kamarudin, Muhammad Ramlee; Hayat, Omar (MDPI AG, 2020)
The narrow bandwidth and low gain performances of a reflectarray are generally improved at the cost of high design complexity, which is not a good sign for high-frequency operation. A dual resonance asymmetric patch reflectarray antenna with a single layer is proposed in this work for 5G communication at 26 GHz. The asymmetric patch is developed from a square patch by tilting its one vertical side by a carefully optimized inclination angle. A progressive phase range of 650◦ is acquired by embedding a circular ring slot in the ground plane of the proposed element for gain improvement. A 332-element, center feed reflectarray is designed and tested, where its high cross polarization is suppressed by mirroring the orientation of asymmetric patches on its surface. The asymmetric patch reflectarray offers a 3 dB gain bandwidth of 3 GHz, which is 4.6% wider than the square patch reflectarray. A maximum measured gain of 24.4 dB has been achieved with an additional feature of dual linear polarization. Simple design with wide bandwidth and high-gain of asymmetric patch reflectarray make it suitable to be used in 5G communications at high frequencies.